New insights into the structure of PINK1 and the mechanism of ubiquitin phosphorylation. (3rd September 2018) - Rasool, Shafqat; Trempe, Jean-François
Abstract: Mutations in PINK1 cause early-onset recessive Parkinson's disease. This gene encodes a protein kinase implicated in mitochondrial quality control via ubiquitin phosphorylation and activation of the E3 ubiquitin ligase Parkin. Here, we review and analyze functional features emerging from recent crystallographic, nuclear magnetic resonance (NMR) and mass spectrometry studies of PINK1. We compare the apo and ubiquitin-bound PINK1 structures and reveal an allosteric switch, regulated by autophosphorylation, which modulates substrate recognition. We critically assess the conformational changes taking place in ubiquitin and the Parkin ubiquitin-like domain in relation to its binding to PINK1. Finally, we discuss the implications of these biophysical findings in our understanding of the role of PINK1 in mitochondrial function, and analyze the potential for structure-based drug design.